Denetimli serbestlik tedbiri konulan madde kullanıcılarında depresyon belirti düzeyine göre bağımlılık şiddetinin incelenmesi - KARACA, SEMRA (My University, 2021)
Objective: The aim of this study was to examine the addiction severity in drug users who were imposed judgment of probation according to depressive symptom level. Method: The descriptive and cross-sectional research was conducted in the sample of drug users (N=330), whose follow-up is continuing by the probation office. The data were collected using the Personal Information Form, Beck Depression Inventory (BDI), and the Addiction Profile Index Clinical Form (API-C). Results: The average age of substance users participating in the study was 28.93 ± 6.96, 97% were male, 40% were secondary school graduates, and 59.1% were single. API-C total/severity score of the participants was 12.32 ± 4.02, 16.7% of them had moderate and 31.8% of them had a high level of addiction severity. According to the BDI cut-off point; API-C total and sub-dimensions scores was statistically significantly higher in substance users who high depressive symptom level. Conclusion: Half of the substance users who are put on probation have low addiction levels. Addiction severity is also high in substance users with high levels of depressive symptoms. In this context, it may be suggested to focus on preventing addiction and early diagnosis and treatment of depressive problems in individuals with substance abuse.

Amaç: Bu çalışmada; denetimli serbestlik tedbiri konulan madde kullanıcılarında depresif belirti düzeyine göre bağımlılık şiddetinin incelenmesi amaçlandı. Yöntem: Kesitsel tipteki araştırma, bir denetimli serbestlik şube müdürlüğünce takip edilen madde kullanıcıları örnekleminde (N=330) yapıldı. Veriler Kişisel Bilgi Formu, Beck Depresyon Envanteri (BDE) ve Bağımlılık Profili İndeksi Klinik Formu (BAPİ-K) ile toplandı. Bulgular: Araştırmaya katılan madde kullanıcılarının yaş ortalaması 28,93±6,96, %97’si erkek, %40’ı ortaokul mezunu, %59,1’i bekardı. Katılımcıların BAPİ-K toplam /şiddet puan ortalaması 12,32±4,02 olup, %16,7’sinde orta ve %31,8’inde yüksek düzeyde bağımlılık şiddeti olduğu belirlendi. BDE kesme noktasına göre, BAPİ-K toplam puanı ve tüm alt boyutlarında depresif belirti düzeyi yüksek olanlar olmayanlara göre istatistiksel olarak anlamlı ölçüde daha yüksek puan aldı. Sonuç: Denetimli serbestlik tedbiri konan madde kullanıcılarının yarısında bağımlılık şiddeti düşüktür. Depresif belirti düzeyi yüksek olan madde kullanıcılarında bağımlılık şiddeti de yüksektir. Bu bağlamda, madde kullanımı olan bireylerde bağımlılığı önlemeye ve depresif sorunların erken tanı ve tedavisine odaklanılması önerilebilir.
Investigation of addiction severity of drug users under probation according to depressive symptom level
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Addiction severity; depressive symptom level; substance users; : Madde kullanıcıları; depresif belirti düzeyi; bağımlılık şiddeti